Urban governance and urban food systems in Africa: Examining the linkages. (October 2016) - Smit, Warren
Abstract: Urban food systems have increasingly been recognised as a topic that needs to be better understood, in order to address issues of urban food security and urban poverty. This is particularly so in Africa, which has high rates of urban population growth and high levels of urban food insecurity. There has, however, been surprisingly little work on examining the existing processes through which urban food systems are governed. In this article, based on a review of the relevant literature, I examine what we know about urban governance and urban food systems in Africa. The governance of urban food systems in Africa is complex, with a range of governance actors with competing agendas. These governance actors impact on urban food systems, and thus on urban food security, in a variety of ways, including: the impact on food production (e.g. urban and peri-urban agriculture); the impact on the distribution of food; the impact on the retail of food by formal and informal traders; and the impact on food safety. There are many gaps in our knowledge about urban governance and urban food systems in Africa, including: processes in secondary cities; the role of, and impact of, local governments on urban food systems; the impact of inadequate transport systems on food distribution; and the impact of supermarkets (and their expanding supply chains) on urban food systems. We need to better understand existing urban governance processes, and their impacts on urban food systems, in order to be able to collaboratively design interventions to improve urban food security in Africa. Highlights: Urban governance can impact on urban food systems and food security in various ways. Our knowledge of the governance of urban food systems in Africa has many gaps. We need to better understand the actual governance of urban food systems in Africa.